Peran dan Hak Masyarakat Dalam Perlindungan dan Pengelolaan Lingkungan Hidup Menurut Undang Undang No 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Kadarudin; Husni Thamrin; Arpina (Collegium Studiosum Journal, 2021)
Humans in utilizing these natural resources must of course pay attention to their goals, and the effects caused by their use, which if left unchecked will have an impact on the growth ecosystem of every existing environment. We need to know that the environment plays a very important role in people's lives, where every community definitely needs a clean and far from pollution environment, one of the roles of the community in maintaining and managing the environment is the creation of the Law on Environmental Protection and Management, hereinafter abbreviated as UUPPLH is a regulation made in order to guarantee the fulfillment and needs of the right to the environment in its protection and management. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.